Effectiveness of a school-based high-intensity interval training intervention in adolescents: study protocol of the PRO-HIIT cluster randomised controlled trial - Liu, Yong; Barker, Alan R.; Adlam, Anna-Lynne R.; Li, Minghui; Duncombe, Stephanie L.; Agbaje, Andrew O.; Gu, Yaodong; Zhou, Huiyu; Williams, Craig A. (Frontiers in Pediatrics, 2024)
High-intensity interval training (HIIT) is an effective strategy for improving a variety of health and fitness outcomes within the school settings. Incorporating HIIT into existing physical activity opportunities appears practically feasible, yet the process evaluation and effectiveness of this strategy needs to be further evaluated. Therefore, a PRO-HIIT intervention will be conducted to evaluate the effectiveness of a 12-week school-based HIIT intervention on cardiorespiratory fitness, physical activity, body composition, muscular strength, bone health, cognitive function, wellbeing and academic performance among 12-13-year-olds.Eight classes of year 7 students (12-13-year-olds) from a secondary school in Ningbo, China, will be recruited and randomly allocated into an intervention or control group. While the control group maintains their usual activities, a 6 to 10-minute HIIT session will be embedded in the physical education or physical activity lessons five days a week for 12 weeks for the intervention group. Training workshops will be conducted for participants, teachers, and research staff for facilitating the intervention. Outcome data will be collected at three time points: pre-and post-intervention, and two months (summer holiday) upon completion of the intervention. Linear mixed models will be used to analyse the impact of groups (intervention and control), timepoints (pre-, post-and two-month after intervention) and group by time interactions. The implementation process of the intervention will be evaluated with the guidance of MRC process evaluation framework.Ethics approval is obtained from the Ningbo University Ethics Committee (TY2024002).Results from PRO-HIIT study will be disseminated via peer-reviewed journals, scientific conferences as well as local education system. The study protocol has been retrospectively registered on ClinicalTrials.gov Protocol Registration and Results System (NCT06374732), https://clinicaltrials.gov/study/NCT06374732.